Avaliação do conhecimento dos profissionais de saúde sobre o programa de cessação do tabagismo - Fabricio, Nadja Fernanda Trefiglio Nais [UNESP] (2015)
Smoking, conceptualized as the act of consuming commercial cigarettes or any tobacco-related product, is currently recognized as a chronic disease, being isolated in tobacco smoke about 4,720 toxic substances, including nicotine causing physical and psychological dependencies and the leading preventable cause of diseases, disability and death worldwide, and smoking prevention and cessation of tobacco use are clinically effective actions and highly effective cost to the public health. It is a current matter of the utmost importance for the health care, however, until now, have not been described studies in Brazil that approach the knowledge of health professionals about the smoking cessation program, for both those who work in basic care, as those who perform activities in the hospital network. The objective of this study was to evaluate the knowledge of health professionals about the smoking cessation program. This is a descriptive, observational, with a quantitative approach. The study evaluated 136 health professionals from basic care and hospital area in the city of Dois Córregos, through structured and self-administered questionnaire. The results of this study showed that most of the individuals were female (87.5%), mean age 40.3 (+ 11.3) years old, schooling until high school (52.9%) and length of professional experience up to 10 years (55.9%). There was a predominance of basic care (68.4%) as workplace and nursing technicians (27.9%) as professional category. Regarding the smoking history, 67% were nonsmokers, 20.5% former smokers and 12.5% smokers. 92.7% of the professionals have never worked in smoking cessation and 47.1% had qualification on the treatment of smoking during the course of vocational training. Knowledge about the treatment was considered insufficient by 66.2% of the participants. The question covering smoking concept was answered incorrectly by 62.5% of the professionals, especially 93.6% of community health ...